Multifocal motor neuropathy. A clinical case and literature review - Laucius, O.; Danielius, V.; Vanagas, T.; Valiukevičius, P. (Neurologijos seminarai, 2023)
Multifocal motor neuropathy is a rare motor neuron disease characterised by a progressive, gradual loss of muscle strength, although sensory functions are preserved. The worldwide frequency of this disease is estimated at 1 person per 100,000 people. MMN is diagnosed when there are characteristic clinical signs, electroneuromyography test results support the clinical findings, and other possible diagnoses are excluded. To prove the progressive course of the disease, the patient must be under long-term medical supervision, since the deteriorating state of the patient may imitate other diseases affecting the motor neuron, such as amyotrophic lateral sclerosis, chronic inflammatory demyelinating polyneuropathy, spinal muscular atrophy, and other. We present the clinical case of a 71-year-old patient who presented to the Neurology Department of the Hospital of Lithuanian University of Health Sciences Kauno Klinikos. She complained of pain in her right hip and progressing weakness of the right foot which had lasted for a year. After laboratory tests, long-term supervision, and exclusion of other diagnoses, the patient was diagnosed with an atypical type of multifocal motor neuropathy responsive to treatment with intravenous immunoglobulin.